TP019/#1556 PICCOLO: an open-label, single arm, phase 2 study of mirvetuximab soravtansine in recurrent platinum sensitive, high-grade epithelial ovarian cancers with high folate-alpha expression. (4th December 2022) - Secord, Angeles Alvarez; Lewin, Sharon; Method, Michael; Murphy, Conleth
Abstract : Objectives: Elevated FRα expression is a characteristic of epithelial ovarian cancer (EOC), thereby an attractive candidate for targeted therapeutic approaches. Mirvetuximab soravtansine is an antibody-drug conjugate (ADC) comprising a FRα-binding antibody, cleavable linker, and maytansinoid DM4, a potent tubulin-targeting agent that has consistently shown clinically meaningful single agent activity, along with favorable tolerability, in patients with high FRα expressing tumors. Methods: PICCOLO is a single arm, phase 2 study designed to evaluate the efficacy of mirvetuximab soravtansine in patients with recurrent platinum-sensitive EOC (including primary peritoneal cancer, or fallopian tube cancer) who, in the opinion of the investigator, are candidates for a non-platinum, single agent therapy for their next line of therapy. Confirmation of high FRα positivity by immunohistochemistry using Ventana FOLR1CDx Assay (high expression; ≥ 75% of cells with PS2+ staining intensity) and 2 prior lines of platinum-based therapy are required for inclusion. Patients with documented platinum allergy require only one prior line of platinum. PICCOLO will enroll 75 patients who will receive intravenous mirvetuximab soravtansine at a dose of 6 mg/kg, calculated using adjusted ideal body weight, on Day 1 of a 21-day cycle. The primary efficacy endpoint is objective response rate (ORR; by investigator) and secondary endpoints include duration of response, progression-free survival, overall survival, CA-125 response, safety and tolerability. PICCOLO is a global study that opened for enrollment in August 2021. Results: Trial in progress: there are no available results at the time of submission. Conclusions: Trial in progress: there are no available conclusions at the time of submission.